Acoustical spectroscopy of carbohydrate aqueous solutions: saccharides; alkyl glycosides; cyclodextrins. Part II. Association and Complexation - KAATZE, Udo (Archives of Acoustics, 2010)
Results from broadband acoustical spectroscopy for aqueous solutions of mono- and disaccharides with salts added, of various alkyl glycosides, and of α-cyclodextrin with n-octyl-β-D-glucopyranoside added are briefly summarized in view of their relevance in the study of molecular association and complexation processes. Mono- and tridentate complexes of alkali earth ions with saccharides are discussed as well as the monomer exchange between micellar structures and the suspending phase in the alkyl glycoside surfactant solutions. Particular attention is given to the behaviour at solute concentrations close to the critical micelle concentration or aggregate concentration, respectively. Also described is the competition between inclusion complex formation and self-aggregation in solutions containing cyclodextrin and alkyl glycoside surfactant.